Implementation of early warning system in Kampung Jenagor, Kuala Berang as an effort to increase human resilience towards flood disaster - Azrul Ghazali,; Sivadass Thiruchelvam,; Kamal Nasharuddin Mustapha,; Rahsidi Sabri Muda,; Nora Dato’ Yahya,; Hasril Hasini,; Ng, Yu Jin; Fatin Faiqa Norkhairi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Residents living downstream of Kenyir dam (Stesen Janaelektrik Sultan Mahmud) are at risk of being flooded due to overflow through spillway, or worst, dam breaks. The nearest community to Kenyir dam is Kampung Jenagor (Kampung Jenagor) residents. A disaster preparedness action plan was proposed to equip the residents with essential knowledge on how to respond to such disaster and how to safely evacuate to designated safe havens. This paper presents one key element of the mentioned action plan, which is to develop and install a flood disaster early warning system. The system is aimed to effectively disseminate warning to Kampung Jenagor residents and ensure that there is a constant state of preparedness. The paper discusses the fundamentals of effective warning dissemination and basic design of Kampung Jenagor’s early warning system.